تطبيق النص الجنائي بين الإقليمية والعالمية في ظل عولمة مكاقحة الجرائم المستحدثة - بن صغير, عبد المومن (جامعة الوادي University of Eloued, 2019)
ملخص المقال: لعبت العولمة دورا هاما في التأثير على جميع مجالات الحياة الاقتصادية والثقافية والاجتماعية،وكذلك على الجانب القانوني، ومن بين تلك فروع القانون التي تأثرت بشكل جلي القانون الجنائي أحد فروع القانون العام. فبالرغم من أن مبدأ إقليمية القانون مازال يشكل أساس القانون الجنائي،فإن ضرورة تحسين أداء القانون الجنائي في مواجهة الجريمة أدت إلى إيجاد قيود على مبدأ الإقليمية، تهدف إلى الحد من الارتباط المطلق للنصوص الجنائية بإقليم الدولة. بالإضافة إلى هذا التطور المتعلق بسريان النصوص الجنائية من حيث المكان،وفقا لمبدأ عالمية النص الجنائي وتطبيق القانون الجزائي الأجنبي الذي تبنته بعض التشريعات،تحاول الدول إيجاد آليات التعاون فيما بينها،لمكافحة الجرائم المستحدثة التي نمت بنمو ظاهرة العولمة. Abstract: Globalization has played an important role in influencing all areas of economic, cultural and social life, as well as on the legal side. Among those branches of law that have been clearly affected by criminal law is a branch of public law.. Although the principle of regional law remains the basis of criminal law, the need to improve the performance of criminal law in the face of crime has led to restrictions on the principle of territoriality, aimed at limiting the absolute link of criminal texts to the territory of the State. In addition to this development concerning the application of criminal texts in terms of place, in accordance with the principle of universality of criminal law and the application of foreign penal law adopted by some legislation, States are trying to find mechanisms of cooperation among themselves to combat the newly created crimes that have grown in the growth of globalization..
The Application Of Criminal Law Between Regional And Global In Light Of The Globalization Of The Scourge Of Modern Crimes
Keywords: القانون الجنائي -العولمة-مبدأ إقليمية القوانين-مبدأ عالمية النص الجنائي-الجرائم المستحدثة; Criminal law - Globalization - The principle of regional laws - The principle of universality of the criminal text - New crimes.